The Ability of Infused Green Tea (Camellia sinensis) in Reducing Oxidative Stress Levels in The Blood of BALB/c Mice Exposed to Electronic Cigarette Smoke - Setiawan, Putri Audrina Arsati; Wahyuniari, Ida Ayu Ika; Linawati, Ni Made; Arijana, I Gusti Kamasan Nyoman (E-Jurnal Medika Udayana, 2025)
Electronic cigarettes allow Reactive Oxygen Species (ROS) in their emissions, and ROS induce oxidative stress. Oxidative stress can be mitigated with antioxidants. Green tea can act as an exogenous antioxidant that can limit the development of free radicals by binding to ROS. This research aims to determine the potential of green tea infusion ( Camellia sinensis ) at doses of 0,03 g/head/day and 0,06 g/head/day in reducing the levels of malondialdehyde (MDA) oxidative stress in the blood of BALB/c mice exposed to electronic cigarette smoke. The research design is an in vivo experimental study with a Randomized Post Test Only Control Group design using 20 male BALB/c mice, divided into four groups: normal control group (KN), negative control group (K-) (exposed to electronic cigarette smoke), treatment group 1 (P1) (exposed to electronic cigarette smoke and given green tea infusion at a dose of 0,03 g/head/day), and treatment group 2 (P2) (exposed to electronic cigarette smoke and given green tea infusion at a dose of 0,06 g/head/day). The results showed a significant and meaningful difference in the mean comparison of malondialdehyde (MDA) levels in the blood of mice in all four groups, K- (14,706 ?m/L) with KN (8,907 ?m/L), P1 (7,069 ?m/L), and P2 (6,654 ?m/L). This study revealed that the administration of green tea infusion at doses of 0,03 g/head/day and 0,06 g/head/day is effective in reducing the levels of oxidative stress in the blood of mice exposed to electronic cigarette smoke. Keywords : electronic cigarettes, green tea, oxidative stress, malondialdehyde